2022
DOI: 10.1212/wnl.0000000000201044
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Cognitive Phenotypes of Patients With Amyotrophic Lateral Sclerosis Carrying SOD1 Variants

Abstract: Background and Objectives:SOD1 variants in patients with amyotrophic lateral sclerosis (ALS) have been associated to peculiar clinical features and disease progression but rarely to cognitive and behavioural impairment. This study aims at describing the features of frontotemporal syndromes in ALS patients carrying SOD1 variants.Methods:Italian patients with ALS were consecutively enrolled between 2012 and 2020 at our Motor Neuron Disease center. All underwent clinical assessment, extensive neurophysiological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
2
2
0
2
Order By: Relevance
“…A more recent paper on 14 ALS‐SOD1 patients reported that behavioral impairment, as defined by the Strong criteria, was more frequent in ALS‐SOD1 than in ALS patients without SOD1 pathogenic variants. It was also suggested that behavioral impairment was more frequent in subjects carrying SOD1 variants in exon 5 24 . In our series, while confirming that behavioral impairment was more frequent in ALS‐SOD1 than in WT‐ALS, we did not observe any difference in frequency based on the involved exon.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A more recent paper on 14 ALS‐SOD1 patients reported that behavioral impairment, as defined by the Strong criteria, was more frequent in ALS‐SOD1 than in ALS patients without SOD1 pathogenic variants. It was also suggested that behavioral impairment was more frequent in subjects carrying SOD1 variants in exon 5 24 . In our series, while confirming that behavioral impairment was more frequent in ALS‐SOD1 than in WT‐ALS, we did not observe any difference in frequency based on the involved exon.…”
Section: Discussionsupporting
confidence: 87%
“…It was also suggested that behavioral impairment was more frequent in subjects carrying SOD1 variants in exon 5. 24 In our series, while confirming that behavioral impairment was more frequent in ALS-SOD1 than in WT-ALS, we did not observe any difference in frequency based on the involved exon. In all these studies, including ours, no SOD1-ALS patients with FTD was identified.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings are in line with several postmortem studies that described lesions of the (extrapyramidal) motor and nonmotor systems in SOD1 -positive cases, including subcortical structures as well as frontotemporal cortices [ 53 , 54 ]. A recent study also revealed that behavioral changes are more commonly found in patients carrying SOD1 variants than previously thought [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive involvement in SOD1 -ALS is seldomly reported. A recent study however suggested that behavioral changes may be more common than previously thought among patients harboring SOD1 variants [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…К ним относится в первую очередь мутация в гене С9ORF72, в меньшей степени -мутации CHCHD10, SQSTM1, TBK1, CCNF и др. [32,33]. Высока частота когнитивно-поведенческих нарушений и при классических формах БАС.…”
unclassified